Discrepancies between actual and perceived abilities in understanding argumentative texts amongst ESL students in Malaysia - Rahim, Mahdalela; Sharifudin, Mohd Azlan Shah; Hamzah, Fazlinda; Bidin, Afidah; Hamid, Nurul Atiqah Abd (International Journal of Asian Social Science, 2024)
The ability to apply classroom learning to real-world contexts is essential, particularly in understanding arguments within argumentative texts. This skill is vital for informed citizenship, as it equips future graduates to handle real-life issues they will encounter in society and industry, fostering lifelong learning beyond their tertiary education. The purpose of this study is to compare students’ actual abilities with their self-assessments in comprehending argumentative texts from newspapers by identifying any discrepancies between students' actual and perceived abilities, enabling instructors to design more effective teaching strategies to bridge these gaps. This study is qualitative in nature whereby it involved 51 diploma-level English as Second Language (ESL) students from a Malaysian public university. Four newspaper articles from local columns were used to test actual comprehension abilities, while an online survey assessed students' self-perceived abilities. Results indicated a significant disparity between actual and perceived abilities, consistent with previous research. Although not explicitly tested, there appears to be a correlation between negative self-assessments and poor performance. Future research should explore the effectiveness of the three-stage model essay framework in preparing students for real-world applications, as this model may not align with industry needs. A new framework is needed to aid ESL students in comprehending not only academic argumentative texts but also authentic texts.